2018
DOI: 10.1152/jn.00552.2017
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus phasic discharge is essential for stimulus-induced gamma oscillations in the prefrontal cortex

Abstract: The locus coeruleus (LC) noradrenergic (NE) neuromodulatory system is critically involved in regulation of neural excitability via its diffuse ascending projections. Tonic NE release in the forebrain is essential for maintenance of vigilant states and increases the signal-to-noise ratio of cortical sensory responses. The impact of phasic NE release on cortical activity and sensory processing is less explored. We previously reported that LC microstimulation caused a transient desynchronization of population act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 90 publications
7
28
0
Order By: Relevance
“…We tested the hypothesis that activation of LC ensembles was accompanied by the activated cortical state. Such a finding would be wholly consistent with prior studies during urethaneanesthesia or during sleep, which examined cortical spectral power after spontaneous increases in LC multi-unit spiking or after LC stimulation (Carter et al, 2010;Marzo et al, 2014;Neves et al, 2018;Hayat et al, 2020). Here, we examined changes in cortical area 24a local field potential (LFP) power triggered on LC ensemble activation times.…”
Section: Diverse Cortical States Are Associated With Activation Of DIsupporting
confidence: 81%
See 1 more Smart Citation
“…We tested the hypothesis that activation of LC ensembles was accompanied by the activated cortical state. Such a finding would be wholly consistent with prior studies during urethaneanesthesia or during sleep, which examined cortical spectral power after spontaneous increases in LC multi-unit spiking or after LC stimulation (Carter et al, 2010;Marzo et al, 2014;Neves et al, 2018;Hayat et al, 2020). Here, we examined changes in cortical area 24a local field potential (LFP) power triggered on LC ensemble activation times.…”
Section: Diverse Cortical States Are Associated With Activation Of DIsupporting
confidence: 81%
“…In order to assess brain state, a single tungsten electrode was placed in cortical area 24a (anterior cingulate cortex) (Paxinos and Watson, 2017) and the mean extracellular field potential (8 kHz lowpass filtered) was recorded in 9 of the 15 rats. Neuronal recordings were made under urethane anesthesia, a widely-used model for studying brain state transitions evoked by LC stimulation (Marzo et al, 2014;Neves et al, 2018). To date, recordings of many LC single units simultaneously in any awake organism with multi-electrode probes has been an intractable problem due to brainstem movement associated with body movement, thus necessitating the use of anesthesia to investigate the relationship between LC ensemble activity and brain state.…”
Section: Resultsmentioning
confidence: 99%
“…To study correlations between evoked LC spiking activity, we applied a single foot shock (5.0 mA, 0.5 ms pulse duration) and measured spike count correlations during the time window of the maximal evoked discharge (50 ms after stimulation; see red spikes in Figure 3A). We used a stimulation intensity that has been shown to elicit a population response (Cedarbaum and Aghajanian, 1978;Devilbiss and Berridge, 2006;Mana and Grace, 1997;Neves et al, 2018;Uematsu et al, 2017;Valentino and Foote, 1987). Mean evoked R SC values were distributed around zero ( Figure 2).…”
Section: Lc Single Units Have Near Zero Spontaneous and Evoked Spike mentioning
confidence: 99%
“…Indeed, simultaneous recordings in the LC and barrel cortex of anesthetized rats combined with dynamical systems modeling showed that activity in the LC was highly predictive of dynamic changes in cortical excitability ( Safaai et al, 2015 ). Moreover, phasic responses in the LC or urethane anesthetized rats were elicited by aversive somatosensory stimuli and modulated the stimulus-induced gamma oscillations in the mPFC, suggesting a corresponding modulation of somatosensory processing ( Neves et al, 2018 ). In awake mice, visual responses have been found to be substantially enhanced during phases when the animals were running compared to no locomotion ( Niell and Stryker, 2010 ).…”
Section: Noradrenergic Modulation Of Sensory Processingmentioning
confidence: 99%